The Impact of Entrepreneurial Orientation on Reducing Turnover Intentions Among Millennial Employees - Soegiarto, Jimmy; Darwin, Muhadjir; Hadna, Agus Heruanto; Junarsin, Eddy; Pelawi, Rizky Yusviento (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2024)
This study investigates Millennials' job expectations concerning company attributes and how these expectations relate to job satisfaction and organizational commitment. PLS-SEM analysis indicates that management support, rewards/reinforcement, work discretion, and resources are aspects of Entrepreneurial Orientation (EO) that correspond to the job expectations of Millennials within organizations. Our finding corroborates the idea that job satisfaction plays a focal role in crafting employee retention strategies by indicating that job satisfaction partially mediates the connection between Millennials' expectations and organizational commitment. This finding suggests that Millennials more likely to evaluate their job satisfaction before decide to stay with or leave the organization.